Creation And The Theology Of Relationship As A Fundamental Theme In The Old Testament - Mawikere, Marde Christian Stenly; Hura, Sudiria (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2025)
This article explores creation and the theology of the God-Humanity-Creation relationship in the Old Testament, highlighting key elements such as the theology of perichoresis, the origin of the human body from the earth (adamah, אֲדָמָה), and the state of creation before and after humanity’s fall. It also examines the consequences of communal transgression and God's promise of restoration. By employing qualitative hermeneutical methods through biblical text analysis and theological literature studies, this study affirms that the work of restoration is a divine initiative aimed at re-establishing harmonious relationships between humanity, creation, and the Creator. This research offers new insights into the significance of restoration within the framework of creation and humanity’s responsibility as stewards of creation, while also presenting hope for the renewal of all creation. The conclusion of this study emphasises that the restoration of the God-Humanity-Creation relationship in the Old Testament is a divine initiative intended to restore the harmony of creation following humanity’s fall. By highlighting the concept of the theology of perichoresis, the origin of humanity from the earth (אֲדָמָה, adamah), and the impact of the fall on creation, this research asserts that restoration is not merely a promise but an ongoing part of God’s plan. Moreover, this study underscores humanity’s role as stewards of creation and provides theological insights into the hope of renewal for all creation in light of God’s redemptive work.